E-lkpd sebagai media digital untuk mendorong keterampilan berpikir kritis peserta didik dalam pembelajaran biologi: Literature review - Rahmawati, Rima Aulia; Suryaningsih, Yeni; Kurnia Sugandi, Muhamad (Papanda Journal of Mathematics and Science Research, 2025)
The development of digital technology in education has driven the transformation of learning media from print to electronic formats. One innovation that is increasingly being used is the Electronic Student Worksheet (E-LKPD), which is designed to be interactive, flexible, and support independent learning for students. This study aims to analyze the literature related to the application of E-LKPD in biology learning in high schools, particularly its role in developing students' critical thinking skills. The method used is a literature review with a narrative review model, analyzing 18 articles published between 2022 and 2025 through the Google Scholar, Garuda, DOAJ, and ResearchGate databases. The analysis was conducted based on the research focus, methods, and relevant key findings. The results of the review show that E-LKPD has been proven to be practical and effective in improving learning outcomes and critical thinking skills. The integration of E-LKPD with innovative learning models such as Problem-Based Learning, Guided Discovery, and scientific approaches can encourage students to analyze, evaluate, and interpret biological concepts in greater depth. Therefore, E-LKPD can be positioned as a strategic digital medium that supports the achievement of 21st-century skills and is in line with the implementation of the Merdeka Curriculum